2024
DOI: 10.3311/ppch.22159
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profiles, in vitro Antioxidants, and Anti-inflammatory Activities of Flowers and Leaves of Lantana camara L. Grown in South of Tunisia

Khadija Ben Othman,
Najeh Maaloul,
Sana Nhidi
et al.

Abstract: The current study assesses the photochemical profiles, the in vitro antioxidant (2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2'-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS), reducing power ferric and silver nanoparticule) and anti-inflammatory activity of Lantana camara L. leaves and flowers collected from the South of Tunisia. Bioactive extracts of two organs were prepared through an ultrasound-assisted extraction in ethanol. Herein, multivariate statistical analysis was performed to define the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
1
0
0
Order By: Relevance
“…The highest concentration of the compound apgienen was at a retention time of 3.98/min, while the lowest concentration was Rutin at a retention time of 5.72/min, as in Tables 4-5 and Figures 3-4. The results were similar to the study [19] on the presence of phenols in flowers and leaves, while the study [20] indicated that the amount of phenols in the methanolic extract of dendritic enamel leaves was 563.57 ± 2.03 mg/g dry weight, while in the methanolic extract of flowers it was 614.79 ± 1.25 mg/g dry weight.…”
Section: Diagnosis Of Phenols By Hplcsupporting
confidence: 88%
“…The highest concentration of the compound apgienen was at a retention time of 3.98/min, while the lowest concentration was Rutin at a retention time of 5.72/min, as in Tables 4-5 and Figures 3-4. The results were similar to the study [19] on the presence of phenols in flowers and leaves, while the study [20] indicated that the amount of phenols in the methanolic extract of dendritic enamel leaves was 563.57 ± 2.03 mg/g dry weight, while in the methanolic extract of flowers it was 614.79 ± 1.25 mg/g dry weight.…”
Section: Diagnosis Of Phenols By Hplcsupporting
confidence: 88%